Novel Hydrophilic Copolymer-Based Nanoparticle Enhances the Therapeutic Efficiency of Doxorubicin in Cultured MCF-7 Cells - Naidu, P.S.R.; Norret, M.; Dunlop, S.A.; Fitzgerald, Melinda; Clemons, T.D.; Iyer, K.S. (AMER CHEMICAL SOC, 2019)
© 2019 American Chemical Society.